The effect of shared leadership on employee resilience: wielding the double-edged sword - Hao, Ma; Min, Yan Ai; Jie, Liu; Yuling, Deng (Frontiers in Psychology, 2025)
IntroductionThis investigation delves into the ambidextrous impacts that shared leadership imparts on the resilience of employees through the incorporation of the Job Demands-Resources framework to delineate the underlying mechanisms. Furthermore, it explores the organizational boundary factors that enhance employees' resilience, so as to explore the ways to improve employees resilience.MethodsThis research chose to use an online questionnaire at two time points with a analysis of 246 valid questionnaires. Surveys were disseminated electronically through esteemed third-party survey platforms so jump.ResultsEmpirical findings illustrate that SLP fosters resilience by bolstering FWA while concurrently heightening role overload and hampering resilience. Furthermore, the study examines how goal clarity modifies these conflicting outcomes. Empirical evidence corroborates the positive moderating role of goal clarity in enhancing the influence of SLP on FWA, and the hypothesized moderating impact of goal clarity on the association between SLP and employees' perception of role overload is also affirmed.DiscussionThis research contributes to the scholarly discourse by illuminating a more comprehensive understanding of the relationship between shared leadership and employee resilience, and further deepens insights into the moderating factors influencing employees resilience by assessing the moderating effect of goal clarity. It also offers practical insights into implementing shared leadership in a manner that harnesses its potential while mitigating its downsides on employee resilience.